Hydrogen induced contact resistance in PERC solar cells - Hamer, P; Chan, C; Bonilla, R; Hallam, B; Bourret-Sicotte, G; Collett, K; Wenham, S; Wilshaw, P (Elsevier, 2018)
The origins of an increase in the series resistance of PERC multicrystalline silicon solar cells due to post-firing thermal processes are investigated. This effect has been shown to be capable of reducing the fill factor of finished cells by up to 20%ABS, severely degrading their performance. It is observed that electric currents applied either during or after these thermal processes can greatly alter the series resistance, either causing it to increase by more than an order of magnitude or suppressing the effect entirely. It is demonstrated that this behavior is in good agreement with the expected interactions of hydrogen with dopants and electric fields within silicon wafers. It is therefore speculated that at least part of the observed increase in resistance is due to the motion of hydrogen within the cell itself.